2002
DOI: 10.1179/joc.2002.14.3.237
|View full text |Cite
|
Sign up to set email alerts
|

In-VitroSusceptibility of Quinolone-Resistant Clinical Isolates ofEscherichia colito Fosfomycin Trometamol

Abstract: Escherichia coli (E. coli) is the most commonly isolated microorganism in uncomplicated lower urinary tract infections (UTI). Due to the increased isolation of E. coli strains resistant to quinolones, it is important to have available alternative drugs to this class of antibiotics as therapy for UTIs caused by this pathogen. Among the large number of currently available antimicrobial agents, fosfomycin trometamol is a useful alternative due to its peculiar microbiological and pharmacokinetic properties. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 7 publications
3
11
0
4
Order By: Relevance
“…1). These results are similar to those described in previous reports of non-ESBLproducing isolates (2,8,14), confirming that fosfomycin retains its activity against ESBL-producing isolates, and cross-resistance with other classes of antimicrobial agents is not a problem at present.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…1). These results are similar to those described in previous reports of non-ESBLproducing isolates (2,8,14), confirming that fosfomycin retains its activity against ESBL-producing isolates, and cross-resistance with other classes of antimicrobial agents is not a problem at present.…”
supporting
confidence: 81%
“…After many years of fosfomycin use, both in Spain and worldwide, fosfomycin continues to be active against the most common uropathogens, and there is a very low incidence of resistant strains in Escherichia coli (about 2%) (2,12,14).…”
mentioning
confidence: 99%
“…In a similar study Goldstein [20] showed that the activity of fosfomycin against uropathogens was superior to ciprofl oxacin, norfl oxacin and cotrimoxazole. Moreover, it has been demonstrated that fosfomycin tromethamine is active in the urine against common uropathogens, including organisms resistant to other antibiotics, such as quinolone-resistant strains of E. coli [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…A clinical success rate up to 90% has been reported by FMT use in ESBL-positive E. coli-related infections [20]. ESBL was detected in 7 E. coli strains that were sensitive to FMT in the present study.…”
Section: Discussionmentioning
confidence: 54%